2020
DOI: 10.1007/s10827-020-00760-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontal eye field inactivation alters the readout of superior colliculus activity for saccade generation in a task-dependent manner

Abstract: Saccades require a spatiotemporal transformation of activity between the intermediate layers of the superior colliculus (iSC) and downstream brainstem burst generator. The dynamic linear ensemblecoding model (Goossens and Van Opstal, 2006) proposes that each iSC spike contributes a fixed minivector to saccade displacement. Although biologically-plausible, this model assumes cortical areas like the frontal eye fields (FEF) simply provide the saccadic goal to be executed by the iSC and brainstem burst generator.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Therefore, either with altered movements and minimally-altered movement commands (Buonocore et al, 2021), or with minimally-altered movements and significantly altered movement commands (this work), there is a dissociation between saccade kinematics and SC motor burst strengths. This is also consistent with evidence that saccades can have similar metrics even after altering SC activity through reversible inactivation of the frontal eye fields (Peel et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, either with altered movements and minimally-altered movement commands (Buonocore et al, 2021), or with minimally-altered movements and significantly altered movement commands (this work), there is a dissociation between saccade kinematics and SC motor burst strengths. This is also consistent with evidence that saccades can have similar metrics even after altering SC activity through reversible inactivation of the frontal eye fields (Peel et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This, along with other evidence (e.g. (Peel, Dash, Lomber, & Corneil, 2020), motivates investigating whether saccade kinematics are indeed dictated by the SC temporal code or not. I approached this question by exploiting a large asymmetry in how the SC represents the upper versus lower visual fields in its visual sensitivity (Hafed & Chen, 2016).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The model also needs to consider other factors like input from other areas. Indeed, Peel et al, 2020 reported that the SC generates fewer saccade-related spikes during FEF inactivation, even for matched saccade amplitudes. Thus, the link between SC motor burst spiking and saccade kinematics is more loose than suggested by the model.…”
Section: Discussionmentioning
confidence: 99%
“…The model also needs to consider other factors like input from other areas. Indeed, Peel et al (2019) reported that the SC generates fewer saccade-related spikes during FEF inactivation, even for matched saccade amplitudes. Thus, the link between SC spiking and saccade kinematics is more loose than suggested by the model.…”
Section: Discussionmentioning
confidence: 99%